Analysis of Unconditional Conservatism and Earnings Quality on financial reporting Practices in Indonesia upon IFRS Convergence / Monica Santi, Evita Puspitasari and Erlane K Ghani. - Santi, Monica; Puspitasari, Evita; Ghani, Erlane K (Universiti Teknologi MARA Cawangan Selangor, 2017)
This study examined the unconditional conservatism and earnings quality as part of corporate governance before and after IFRS convergence in Indonesia. Specifically, this study looked at the effect of eliminating the conservatism concept within the accounting framework, following thedevelopment of principles-based accounting standards and earnings quality on financial reporting practices. This study further examined the effect of eliminating the conservatism concept towards the earnings quality upon implementation of IFRS convergence on the financial reporting practices. Using content analysis on 180 annual reports of 36 manufacturing listed companies over a 5-year period in Indonesia, this study found that unconditional conservatism has not changed significantly after IFRS convergence. However, the earnings quality of the manufacturing companies has declined upon IFRS convergence. This study also found that unconditional conservatism has a positive influence on earnings quality upon IFRS convergence although the result is insignificant. From the agency theory’s perspective, this study highlighted the introduction of accounting and governance reform on the principal-agent relationship in relation to the unconditional conservatism and earnings quality practices. The findings in this study shed some light to the regulators, practitioners and other interested parties on the implication of IFRS convergence in a developing country such as Indonesia.